Effects of Microbial Inoculant on Physical and Chemical Properties in Pig Manure Composting. (15th December 2017) - Xu, Pengxiang; Li, Ji
ABSTRACT: Effects of one commercial microbial inoculant (named VT microbial inoculant) on the composting of pig manure were studied. Two treatment piles were prepared in this study, in which one pile was inoculated with VT and another pile without VT. The results indicated that inoculation could accelerate the temperature rising at the start of composting. Based on the chemical parameters, the VT treatment showed higher N, P2 O5, K2 O, and macronutrient (NPK) content than the CK treatment. The statistical analysis showed that the P2 O5, K2 O, and NPK content had a significant difference ( P < 0.05) between VT and CK treatments at the end of composting, which showed that VT inoculant accelerated the transformation of macronutrient in the end compost product. The changes of total organic carbon indicated that VT additive could accelerate the decomposition of organic carbon, which had a significant difference ( P = 0.023) compared with CK. At the end of the composting, the germination index value of VT treatment (80%) was higher than the control (60%). These results suggested that the inoculation of VT microbial agent was a feasible strategy to convert animal wastes into compost efficiently.